2008
DOI: 10.1097/meg.0b013e3282faa759
|View full text |Cite
|
Sign up to set email alerts
|

Plasma thrombin-activatable fibrinolysis inhibitor and plasminogen activator inhibitor-1 levels in inflammatory bowel disease

Abstract: PAI-1 plasma levels are increased whereas TAFI levels are decreased in IBD patients. These results suggest an imbalance of fibrinolysis in IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 18 publications
3
34
0
Order By: Relevance
“…Although UC patients with active and inactive states were reported to be different in the study by Saibeni et al, a unique point of our study is that we demonstrated the transition of TAFI levels from active stage to remission stage in each UC patient. Contrary to these find- ings, Koutroubakis et al (1) reported a decrease in the TAFI levels versus an increase in plasminogen activator inhibitor-1 (PAI-1) in IBD patients. The authors speculated that this was due to activation of the TAFI pathway, leading to an imbalance in fibrinolysis.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Although UC patients with active and inactive states were reported to be different in the study by Saibeni et al, a unique point of our study is that we demonstrated the transition of TAFI levels from active stage to remission stage in each UC patient. Contrary to these find- ings, Koutroubakis et al (1) reported a decrease in the TAFI levels versus an increase in plasminogen activator inhibitor-1 (PAI-1) in IBD patients. The authors speculated that this was due to activation of the TAFI pathway, leading to an imbalance in fibrinolysis.…”
Section: Discussionmentioning
confidence: 81%
“…In both forms of the disease, a hypercoagulable state and a prothrombotic condition exist, whereas abnormalities in the coagulation system are partially responsible for the clinical picture. The regulation between coagulation and fibrinolysis plays an important role in preserving a balanced hemostatic process, and it is generally accepted that both have been found to be upregulated in active and inactive states of IBD (1,2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, more studies are needed to evaluate a possible defect in kallikreinkallistatin balance in IBD. Hypofibrinolysis process that prevails in IBD is a consequence of the reduction in fibrinolysis proteases activators (see previous paragraph), and could be explained by an increase in fibrinolysis proteases inhibitors, such as SerpinE1 or PAI-1 (plasminogen activator inhibitor) [84]. In that context, the level of SerpinC1 (antithrombin or antithrombin III), which is a potent endogenous thrombin inhibitor, is significantly decreased in the plasma of IBD patients [85,86].…”
Section: Serpinsmentioning
confidence: 99%
“…Recently discovered thrombin activatable fibrinolysis inhibitor (TAFI) provides link between coagulation and fibrinolysis (Bouma, 2004), and primarily its levels have been linked with thrombophilia in IBD. However TAFI plasma level in IBD is equivocal thus its significance is unclear (Koutroubakis et al, 2008;Saibeni et al, 2004). In addition, Italian group (Saibeni et al, 2006) has been demonstrated a prevalence of anti -t-PA antibodies in IBD patients which may reduce systemic fibrinolysis.…”
Section: Systemic Fibrinolytic Capacitymentioning
confidence: 99%